Developing the Workforce, Shaping the Future : Transformation of Madagascar's Post-basic Education - Bashir, Sajitha (World Bank, 2012)
Sub-Saharan African countries are increasingly recognizing the contribution of post basic education to economic growth and social development. However, policy makers in many poor countries struggle to balance expansion and upgrading of post-basic education reform against competing development priorities. They must consider how and sometimes whether, to fund post-basic education in the face of demographic growth, limited public resources, and political and social imperatives. In its new poverty reduction and growth strategy, the Madagascar Action Plan (MAP), the Government of Madagascar made the transformation of its education system one of the key pillars of its development agenda. An important decision was the reform of basic education, covering primary and junior secondary education, including extension of the basic education cycle to 10 years. The Government's new Education for All (EFA) plan provides the policy framework and operational strategies for basic education, covering changes to curricula and learning materials, teaching methods and student assessment. The EFA plan was endorsed by donors and the reform of basic education launched in 2008.The main purpose of this report is to provide analytical inputs for the development of post-basic education reforms. Specifically, the report identifies and prioritizes: (i) the need for change in the structure, content and delivery of Madagascar's post-basic education and training system, and (ii) the key reforms in financing, governance and sub-sector management required to support changes to the structure, content and delivery of the post-basic system.